IRE1 regulates the proteostasis of TDP-43/TARDBP in ALS/FTD through ribosome-associated quality control - Dongyue Liu; Yu Li; Shuai Huang; Yufang Xu; Lei Sun; Wen Li; Cahir J. O’Kane; David C. Rubinsztein; Bingwei Lu; Shuangxi Li (Proceedings of the National Academy of Sciences, 2026)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are progressive neurodegenerative disorders characterized by motor neuron degeneration, leading to muscle weakness, atrophy, and cognitive impairments. A defining pathological hallmark of ALS/FTD is the cytosolic mislocalization and accumulation of TAR DNA-binding protein 43 (TDP-43), highlighting its critical role in ALS pathogenesis. However, the molecular mechanisms underlying TDP-43 proteostasis remain poorly understood. Through a genetic screening approach, we identify inositol-requiring enzyme 1 (IRE1), an endoplasmic reticulum-resident transmembrane protein, as a potent suppressor of TDP-43 protein levels. Furthermore, we show that ribosome-associated quality control (RQC) factors play a crucial role in regulating TDP-43 proteostasis and cellular toxicity. Activation of the RQC pathway prevents excessive accumulation of TDP-43 and associated toxicity. Mechanistically, our findings suggest that IRE1 regulates TDP-43 protein level by promoting the degradation of aberrant TDP-43 translation product through the RQC pathway. IRE1 acts canonically to enhance the transcription of the RQC core component Clbn/NEMF and noncanonically to physically interact with Clbn/NEMF, thereby ameliorating TDP-43-induced proteotoxicity. Moreover, ectopic expression or pharmacological activation of IRE1 alleviates TDP-43 pathology and restores cognitive function in the TDP-43 A315T ALS mouse models. Collectively, our study identifies a role for IRE1 in the translational quality control of TDP-43 and establishes its potential as a therapeutic target for ALS/FTD.